Использование высокотемпературной пайки при создании высокопрочных конструкций - Вакуленко, К. В.; Сотрихин, С. Ю.; Чернобрывко, М. В. (НТУ "ХПИ", 2004)
The problem of connection of two thick cores is considered. The équation of non-stationary heat conductivity is solved. Results of the decision allow to estimate necessary temperature conditions of the soldering of constructional elements.
Keywords: транспортное машиностроение; прочностные свойства швов; сварной шов; термонагружения; высокотемпературные припои; теплопроводность конструкций